Zika epidemic and microcephaly in Brazil: Challenges for access to health care and promotion in three epidemic areas. - Paulo Cesar Peiter; Rafael Dos Santos Pereira; Martha Cristina Nunes Moreira; Marcos Nascimento; Maria de Fatima Lobato Tavares; Vivian da Cruz Franco; José Joaquin Carvajal Cortês; Daniel de Souza Campos; Christovam Barcellos (PLoS ONE, 2020)
Since 2015 Brazil has experienced the social repercussions of the Zika virus epidemic, thus raising a debate about: difficulties of diagnosis; healthcare access for children with Zika Congenital Syndrome (ZCS); the search for benefits by affected families; social and gender inequalities; and a discussion on reproductive rights, among others. The objective of this article is to analyse access to specialized health services for the care of children born with ZCS in three North-eastern states of Brazil. This is an exploratory cross-sectional study which analyses recorded cases of microcephaly at the municipal level between 2015 and 2017. Most of the cases of ZCS were concentrated on the Northeast coast. Rio Grande do Norte and Paraiba had the highest incidence of microcephaly in the study period. The states of Bahia, Paraiba and Rio Grande do Norte were selected for their high incidence of microcephaly due to the Zika Virus. Socio-territorial vulnerability was stratified using access to microcephaly diagnosis and treatment indicators. The specialized care network was mapped according to State Health Secretaries Protocols. A threshold radius of 100 km was stablished as the maximum distance from municipalities centroids to specialised health care for children with microcephaly. Prenatal coverage was satisfactory in most of the study area, although availability of ultrasound equipment was uneven within states and health regions. Western Bahia had the lowest coverage of ultrasound equipment and lacked health rehabilitation services. ZCS's specialized health services were spread out over large areas, some of which were outside the affected patients' home municipalities, so displacements were expensive and very time consuming, representing an extra burden for the affected families. This study is the first to address accessibility of children with microcephaly to specialised health care services and points to the urgent need to expand coverage of these services in Brazil, especially in the northeastern states, which are most affected by the epidemic.